Peningkatan kemampuan bahasa Inggris pada siswa melalui pendekatan multimedia dan strategi pembelajaran inovatif - Maesaroh, Maesaroh (Maliki Interdisciplinary Journal, 2023)
This article discusses efforts to improve student's English speaking skills through the application of multimedia approaches and innovative learning strategies. This approach is underpinned by various references that review effective strategies and methods for developing students' speaking skills. Previous research has highlighted the importance of using audio-visual media, local-based learning, and strategies such as storytelling and word mapping in language learning. This article examines the benefits of incorporating these strategies to create a more diverse and interactive learning experience for students. The aim is to illustrate innovative ways of improving students' English speaking skills through a multimedia approach that utilizes audio-visual media, local wisdom, and storytelling and word mapping techniques. By applying a combination of these strategies, students are expected to be more engaged and motivated in the learning process. This article seeks to provide guidance for educators to create a stimulating and engaging learning environment and contribute to the understanding of the application of innovative learning strategies in the context of English speaking.